The Effect of Coronavirus Exposure on CEO Perceptions of Climate Change - Zhang, Jin; Liu, Yong (Frontiers in Psychology, 2022)
CEOs’ personal experiences can influence their perceptions of climate change and their firms’ pro-environmental behavior; a concept termed the experience-perception link. Thus, the experience of the recent COVID-19 pandemic may have caused a change in CEOs’ perceptions of another global threat—climate change. We test this hypothesis by comparing survey measures of climate risk perceptions, self-efficacy, and pro-environmental behaviors among 605 randomly selected CEOs in Wuhan across three phases—1) before, 2) after the COVID-19 outbreak in Wuhan, and 3) after the COVID-19 had been primarily controlled in Wuhan but was declared a pandemic by the WHO. Harnessing between- and within-subjects variation in COVID-19 exposure, we find a substantial increase in climate change beliefs and actions after the COVID-19 evolved from an epidemic to a pandemic, regardless of subjects’ exposure to the pandemic. We also demonstrate that this change is due to the salience of the global crisis and the feeling of hope elicited by observing effective responses to the crisis, rather than personal experiences solely made from a local health crisis. Our results reveal unexpectedly positive side effects of the abrupt shifts in CEOs’ beliefs and their firms' pro-environmental behaviors in response to the COVID-19 pandemic.